The Qanun Jinayat Discriminates Against Women (Victims of Rape) in Aceh, Indonesia - Faradilla Fadlia; Ismar Ramadani (Journal of Southeast Asian Human Rights, 2018)
This paper seeks to see how the Qanun Jinayah discriminates against women who are victims of rape. In Qanun Jinayah in article 52, paragraph 1, explain that the victim of rape must include evidence at the time of report. The Qanun Jinayah clearly makes a double burden on the victims where women victims of rape must present evidence and witnesses. Whereas in the criminal law (KUHP), evidence and witnesses are the responsibility of the investigator. This study seeks to see how the discriminatory impacts experienced by victims (women) after the Qanun Jinayah is implemented. Furthermore, this paper uses qualitative method with in-depth interview. The hypothesis of this paper is that Qanun Jinayah has discriminated against women especially the victims of rape and this allows the occurrence of injustice and violation of human rights.